Influence of temperature changes in various regions of Turkey on powers of photovoltaic solar panels. Issue 4 (16th February 2016) - Yelmen, Bekir; Çakir, M. Tarik
ABSTRACT: Renewable sources of energy, which are significant alternatives for every nonrenewable energy sources, can be converted to electric energy by productive rotations. Although Turkey is the country that has pretty high solar energy potential when compared to samples in the world, it has facilities still remarkably below required structuring. Demand for solar energy applications that is included in renewable sources of energy is increasing gradually. In Turkey, according to results received by the averages of long periods, approximately 2.68% power loss has been substantiated in powers of photovoltaic panel. Here, it is obviously observed that the East Anatolian region is the most convenient district for panel powers of environmental temperature averages. Turkey is involved in between countries that may take advantage from solar energy and annual average sunshine duration is 2, 640 hours in the country. A heat factor occurs by the absorption of sun beams, which comes to solar panels and affects the power of the panels. In this study, the influence of losses occurring from temperature differences in various regions of Turkey on power of photovoltaic solar panels has been examined and proposals have been progressed in order to reduce losses down to a minimum in electrical systems to be established for this aim.